Sheep farms in the Spanish rangelands (dehesas): Typologies according to livestock management and economic indicators - Gaspar, P.; Escribano, M.; Mesías, F. J.; Ledesma, a Rodriguez De; Pulido, F. (Small Ruminant Research, 2008)
Forty-six dehesa sheep farms of Extremadura (SW Spain) were analyzed on the basis of previously determined technical and economic indicators. A principal component analysis gave ﬁve principal components – related to intensiﬁcation, proﬁtability, and livestock mix – that characterized the farms. Using multivariate techniques based on these factors, a farm typology was established with six categories—three of sheep alone at different levels of intensiﬁcation, and three of sheep in combination with beef cattle or Iberian pig. This typology enabled homogeneous groups of farms to be considered for possible administrative actions relating to their optimal dimensions and stocking rates
Keywords: Dehesa; Farm typology; Principal component analysis; Sheep; technical and economic management

Economic and management characterization of dehesa farms: implications for their sustainability - Gaspar, P.; Mesías, F. J.; Escribano, M.; Rodríguez de Ledesma, A.; Pulido, F. (Agroforestry Systems, 2007)
Dehesa agroforestry systems occupy around 6 million ha in the Iberian Peninsula. Their economic and environmental sustainability depends on the maintenance of the extensive livestock farms which created this typical ecosystem. This work analyzes dehesa farms in the Extremadura region (SW Spain) using technical and economic indicators of 69 randomly selected holdings. Principal component analysis (PCA) allowed us to establish a valid model explaining 65.8% of the variance. The two principal components having most weight were Iberian pig production (explaining 20% of the variance of the model), and which ruminant species were raised on the farm (15% of the variance). A cluster analysis distinguished ﬁve types of farms: sheep farms at high and low stocking rates, beef cattle farms, wooded farms with mixed livestock, and farms with a high level of cropping activity. The most proﬁtable farms were those with either high overall livestock density or a high level of Iberian pig production. While high stocking density has historically attracted high levels of subsidy, production of Iberian pigs was proﬁtable because of the high value of the product. In the light of CAP reform, Iberian pig production seems the most readily sustainable type of farming for the dehesa system.
Keywords: cluster analysis; Farm typology; Livestock farming systems; Principal component analysis; Rangeland management